Volume 3: Heat Transfer; Electric Power 1985
DOI: 10.1115/85-gt-83
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Analysis of Boundary Layer Transition Data for Turbine Application

Abstract: A Symposium on Transition in Turbines was held recently at the NASA Lewis Research Center. One recommendation of the working groups was the collection of existing transition data to provide standard cases against which models could be tested. This paper represents a preliminary response to that recommendation. A number of data sets from the open literature that include heat transfer data in apparently transitional boundary layers, with particular application to the turbine environment, were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Since the existing transition models incorporated in the code do not adequately describe the transition phenomenon under turbomachinery condition, a quantitative prediction remains questionable. Test studies reported by Gaugler (1985) show that, without the exact knowledge of the transition start point and length, with STAN5, a number of iterations must be performed until a reasonable agreement between computed and measured results is obtained. The results presented in this report indicate that the existing boundary layer calculation methods in integral or differential form cannot be considered as a reliable a priori predictive design tool unless the basic mechanisms mentioned above are completely described and implemented into the calculation procedure.…”
Section: Necessity For Experimental Researchmentioning
confidence: 99%
“…Since the existing transition models incorporated in the code do not adequately describe the transition phenomenon under turbomachinery condition, a quantitative prediction remains questionable. Test studies reported by Gaugler (1985) show that, without the exact knowledge of the transition start point and length, with STAN5, a number of iterations must be performed until a reasonable agreement between computed and measured results is obtained. The results presented in this report indicate that the existing boundary layer calculation methods in integral or differential form cannot be considered as a reliable a priori predictive design tool unless the basic mechanisms mentioned above are completely described and implemented into the calculation procedure.…”
Section: Necessity For Experimental Researchmentioning
confidence: 99%
“…For the Reynolds number range encountered in gas turbines, the profile boundary layers are highly transitional, and the usual simplifying assumption that the profile layers are turbulent from the leading edge onward is generally wrong and not necessarily conservative (Gostelow, 1983). Besides being a requirement in predicting profile losses, knowledge on the state of the profile boundary layer is also necessary for the design of efficient blade cooling systems (Gaugler, 1985).…”
Section: P -Pressurementioning
confidence: 99%
“…Wittig and his coresearchers (Wittig et al 1988, Dulenkopf 1992) conducted a series of extensive studies investigating the wake effect on the gas turbine heat transfer. Investigations by Gaugler (1985) and Schobeiri, et al (1991) show that the existing correlations primarily developed for external aerodynamics applications are not capable of correctly predicting the unsteady transition behavior of gas turbine blades. The detailed study by Mayle (1991) and the follow up discussion by Walker (1993) underscore the role and the significance of transition in turbomachinery.…”
Section: Introductionmentioning
confidence: 99%